Evidence for a new pathway in the bacterial degradation of 4-fluorobenzoate. - Oltmanns, R H (1989)
Six bacterial strains able to use 4-fluorobenzoic acid as their sole source of carbon and energy were isolated by selective enrichment from various water and soil samples from the Stuttgart area. According to their responses in biochemical and morphological tests, the organisms were assigned to the genera Alcaligenes, Pseudomonas, and Aureobacterium. To elucidate the degradation pathway of 4-fluorobenzoate, metabolic intermediates were identified. Five gram-negative isolates degraded this substrate via 4-fluorocatechol, as described in previous studies. In growth experiments, these strains excreted 50 to 90% of the fluoride from fluorobenzoate. Alcaligenes sp. strains RHO21 and RHO22 used all three isomers of monofluorobenzoate. Alcaligenes sp. strain RHO22 also grew on 4-chlorobenzoate. Aureobacterium sp. strain RHO25 transiently excreted 4-hydroxybenzoate into the culture medium during growth on 4-fluorobenzoate, and stoichiometric amounts of fluoride were released. In cell extracts from this strain, the enzymes for the conversion of 4-fluorobenzoate, 4-hydroxybenzoate, and 3,4-dihydroxybenzoate could be detected. All these enzymes were inducible by 4-fluorobenzoate. These data suggest a new pathway for the degradation of 4-fluorobenzoate by Aureobacterium sp. strain RHO25 via 4-hydroxybenzoate and 3,4-dihydroxybenzoate.